Pengaruh Pendekatan Jelajah Alam Sekitar terhadap Pemahaman Konsep IPS Siswa Kelas IV SDN 212 Harapan: Penelitian - Siti Umi Hani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to determine the effect of an environmental exploration approach on elementary school students' understanding of social studies concepts. This study uses a nonequivalent pre-test post-test control group design, which is a form of quasi-experimental research method. The population in this study is all fourth-grade students. The sample in this study is class IVA as the experimental class using the JAS approach and IV B as the control class receiving instruction with the lecture method. Data was collected through pre-tests and post-tests. The average score of social studies concept understanding for the experimental class pre-test is not much different from the average score of the control class, which are 64.23 and 65.96, respectively. The difference between the two classes is not too large, which concludes that both classes have similar initial abilities in understanding social studies concepts. After the learning was conducted, the average understanding of social studies concepts in the experimental class was 76.15. Meanwhile, the average post-test score for the control class was 74.62. It can be concluded that the understanding of social studies concepts by students in the experimental class is higher compared to the control class.